2020
DOI: 10.1186/s12864-020-07208-3
|View full text |Cite
|
Sign up to set email alerts
|

Moose genomes reveal past glacial demography and the origin of modern lineages

Abstract: Background Numerous megafauna species from northern latitudes went extinct during the Pleistocene/Holocene transition as a result of climate-induced habitat changes. However, several ungulate species managed to successfully track their habitats during this period to eventually flourish and recolonise the holarctic regions. So far, the genomic impacts of these climate fluctuations on ungulates from high latitudes have been little explored. Here, we assemble a de-novo genome for the European moos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 87 publications
7
45
3
Order By: Relevance
“…In terms of contiguity and accuracy (BUSCO analysis; Table 1), this new genome assembly compares very well with other recent genome assemblies for livestock species such as chicken (W. C. Warren et al 2017) or other wild species such as the grizzly bear (Taylor et al 2018) or sea otter (Jones et al 2017) and was superior to those of other Cervidae species (Dussex et al 2020;Upadhyay et al 2020). Notably, the highest quality genome assemblies (including the present one) are usually obtained when different sequencing strategies are used, including long reads and linked reads, often in combination with typical short-read sequencing (Wallberg et al 2019;Kongsstovu et al 2019).…”
Section: Genome Assembly Using Different Technologiessupporting
confidence: 58%
“…In terms of contiguity and accuracy (BUSCO analysis; Table 1), this new genome assembly compares very well with other recent genome assemblies for livestock species such as chicken (W. C. Warren et al 2017) or other wild species such as the grizzly bear (Taylor et al 2018) or sea otter (Jones et al 2017) and was superior to those of other Cervidae species (Dussex et al 2020;Upadhyay et al 2020). Notably, the highest quality genome assemblies (including the present one) are usually obtained when different sequencing strategies are used, including long reads and linked reads, often in combination with typical short-read sequencing (Wallberg et al 2019;Kongsstovu et al 2019).…”
Section: Genome Assembly Using Different Technologiessupporting
confidence: 58%
“…Similar to previous studies [ 10 , 12 , 13 , 14 ], our geographical distribution of haplogroups ( Figure 3 b) showed that Siberian roe deer from Central Europe to East Asia are highly heterogeneous without clear geographical separation of maternal lineages. This feature might be derived from substantial gene flow due to the high mobility of this species [ 9 , 56 ], as well as high levels of connectivity among populations during the Ice Age [ 33 ]. Furthermore, we found that taking Lake Baikal as the boundary, except the isolated population SKJ, the western populations mainly belong to haplogroups B and C, while all haplogroups are found in the eastern populations, suggesting a different haplogroup composition of populations on both sides of Lake Baikal.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the anthropogenic and natural threats moose currently face, future studies concerned with moose genetic diversity might benefit from the investigation of functional genetic diversity, or the measure of diversity of potentially adaptive markers, by using RNA-seq and wholegenome resequencing (WGR) methods (Brodie et al 2021). This could be accomplished using the recently sequenced European moose genome (Dussex et al 2020), or optimally, by first sequencing the nuclear genome of the North American moose, and then looking to see which SNPs/genes appear most impacted. Understanding both the genomic and transcriptomic characteristics of successful moose subpopulations, particularly in the face of increasing stressors, may highlight which genes or genomic regions are influencing their adaptive capacity.…”
Section: Future Directions and Implications On Conservationmentioning
confidence: 99%